Hierarchical Multiparty Digital Signature for Distributed Systems: Application in Intelligent Vehicle Surveillance - Samir Guediri; Messaoud Abbas; Mostefa Kara; Muath AlShaikh (Journal of Cybersecurity and Privacy)
The rapid expansion of distributed systems such as the Internet of Things (IoT) has increased the need for robust authentication and data integrity mechanisms to ensure public security in dynamic environments. This article presents a hierarchical multiparty digital signature (HMPS) technique designed to address the unique challenges of resource-constrained and decentralized systems. By integrating a modified ElGamal-based individual signature with linear encryption and hierarchical aggregation, HMPS delivers enhanced security through collaborative and layered signing processes. A key application is demonstrated in intelligent vehicle surveillance, where the scheme ensures the authenticity and integrity of commands and data in multi-level communication scenarios. Comprehensive security analysis confirms resistance to forgery, single points of failure, and unauthorized access. HMPS exhibits superior computational efficiency, scalability, and energy efficiency, as evidenced by comparative performance evaluations with state-of-the-art techniques. These results highlight HMPS as a highly effective solution for secure, real-time IoT applications, providing a pathway to more resilient and trustworthy distributed systems.